Occurrence and source apportionment of halogenated flame retardants in the indoor air of Nepalese cities: Implication on human health - Yadav, Ishwar Chandra; Devi, Ningombam Linthoingmabi; Li, Jun; Zhang, Gan (Atmospheric environment (1994), 2017)
Elevated level of brominated- and chlorinated-flame retardants (FRs) have been accounted in ambient air across the globe. Despite what might be expected, restricted information is available on PBDEs and other halogenated FR contained indoor air in whole of Indian sub-continent especially in case of Nepal, sandwiched between two most populous countries i.e. India and China. It was conjectured that the level of halogenated flame retardant (HFRs) in Nepalese air would be high because they have not been liable to control in Nepal; and henceforth there is more plausibility of HFRs to be available in a diverse array of goods and consumer products. This study therefore aims to measure the occurrence, spatial distributions and sources of 15 brominated- and 2 chlorinated-FRs in indoor air from four major cities of Nepal. The overall concentrations of HFRs ranged from 16.1 to 6750 pg/m3 (median 334 pg/m3). The total concentrations of novel brominated fire retardants (NBFRs) were 20 and 100 times (13.2–6270 pg/m3) higher than PBDEs (2.2–353 pg/m3) and DPs (0.67–129 pg/m3), respectively indicating much higher usages of NBFRs in Nepal. The level of ∑PBDEs in air is identified with utilization of wide variety of consumers products and building materials containing FRs in Nepalese houses, while higher concentration of BDE-209 were subject to emission from materials containing deca-BDE formulation. Significantly higher concentrations of DBDPE than BDE-209 in air demonstrated a move to more prominent use of DBDPE as alternative to BDE-209. The lower fanti ratios suggests the DP level in this study was essentially affected by the long range atmospheric transport from remote DP source instead of commercial products. The exposure to BDE-47, -99, −153, −209 and HBB via inhalation was 3–4 orders of magnitude lower than corresponding RfD values, suggesting insignificant risk to Nepalese population. However, other modes of human exposure might still be significant in Nepal. [Display omitted] •Extremely high level of NBFRs detected in air than PBDEs and DPs.•The most detectable NBFR was DBDPE while BDE 209 significantly contributed ∑PBDEs.•Lower fanti ratios indicated DP level was influenced by LRAT from remote source.•Exposure to HFRs via inhalation suggested minimal risk to Nepalese population.